(untitled) (Journal of Artificial Intelligence & Research, 2024)
In the era of Industry 4.0, businesses are increasingly turning to AI-powered customer 360 solutions to personalize customer engagement. This paper delves into the implementation of such solutions, exploring strategies and applications that leverage big data analytics, machine learning, and customer intelligence. By seamlessly integrating data from various touchpoints, organizations can deliver tailored experiences that enhance customer satisfaction and loyalty. The abstract will provide insights into the importance and implications of personalizing customer engagement in Industry 4.0 ecosystems, highlighting key methodologies and technologies driving this transformation.